2017
DOI: 10.1080/21623945.2017.1287638
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol does not directly regulate adipose lipolysis

Abstract: The mechanisms by which estradiol modulates adipose lipolysis are poorly understood. We sought to measure basal and b 3 -stimulated indices of lipoysis (FFAs, glycerol) in vivo in E2 deficient or supplemented rats, and ex vivo with direct acute E2 exposure. For 2 weeks, ovariectomized (OVX) and OVX rats treated with a daily oral dose of E2 (OVX E2) were pairfed to SHAM controls (n D 12 per group). Adipocyte size was modestly (»40%) increased in OVX rats, but did not reach significance (p D 0.2). After 2 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
6
0
3
Order By: Relevance
“…Other in vivo work 4 has demonstrated significant metabolic and physiological effects using a similar injection dose of ghrelin. Also, previous work in our lab 13 has demonstrated a robust increase in lipolysis following CL administration by 30 min. As such, this time point was used for blood and tissue collection.…”
Section: In Vivo Lipolysis and Signalingmentioning
confidence: 53%
See 1 more Smart Citation
“…Other in vivo work 4 has demonstrated significant metabolic and physiological effects using a similar injection dose of ghrelin. Also, previous work in our lab 13 has demonstrated a robust increase in lipolysis following CL administration by 30 min. As such, this time point was used for blood and tissue collection.…”
Section: In Vivo Lipolysis and Signalingmentioning
confidence: 53%
“…Previous work has found that these doses for AG, UnAG and CL elicit significant metabolic effects; the dose used for GH represents a concentration that is achieved in response to ghrelin administration in rats. 7,10,13 Sampling of media for the quantification of glycerol and free fatty acids was done at t = 2, 4 and 8h. Aliquots were immediately frozen at −80°C for further analysis.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Treatment with E2 decreases obesity[ 276 ], protects against hepatic steatosis[ 277 ], lowers the activity of cholesterol acyl-transferase[ 278 ] and limits fat deposition[ 279 ]. All these are –again– indirect actions aimed to decrease the storage of excess TAG, since E2 does not directly regulate lipolysis[ 280 ]. Nevertheless, estrogens decrease lipogenesis[ 281 ] in WAT; and adipogenesis is also inhibited through ERα activation[ 282 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to suppressing lipogenesis and lipogenic gene expression (i.e., inhibiting adipogenesis), estrogen is reported to promote both basal and catecholamine-induced lipolysis [37], with a reduction in lipoprotein lipase activity observed in women with low estrogen levels [13]. However, this contrasts with a recent study using pair-fed OVX versus OVX + estrogen supplemented groups and surgical controls, which found no effect of estrogen on lipolysis in either visceral or subcutaneous depots by a number of different measures [38]. When considering the potential role of estrogen in metabolic flexibility of white adipose tissue, it is clear that additional context-dependent variables remain to be fully addressed.…”
Section: Estrogen and Sex-dependent Adipose Tissue Distribution Fmentioning
confidence: 99%